Improving the cooling performance of photovoltaic panels by using two passes circulation of titanium dioxide nanofluid. (August 2022) - Murtadha, Talib K.; dil Hussein, Ali A.; Alalwany, Ahmed A.H.; Alrwashdeh, Saad S.; Al-Falahat, Ala'a M.
Abstract: The major goal of this study is to achieve the cooling effect of a photovoltaic panel by employing titanium dioxide nanofluid as a cooling fluid in two passes circulation to lower the panel surface temperature, improve the performance of the photovoltaic/thermal system, and increase efficiency. Photovoltaic technology is constantly losing efficiency due to the high temperature of the PV panel's upper surface, which results in lower output power and lower overall efficiency. Five photovoltaics panels were utilized in this investigation to compare the three concentrations of Titanium Oxide nanofluid (1 wt%, 2 wt%, 3 wt%), as well as cooling by water and an uncooled penal. The output powers were (44.5, 44, 43.2, 42.6, and 39.5 W) when the three concentrations of Titanium Oxide nanofluid (3 wt%, 2 wt%, and 1 wt%) were used, then water cooled and uncooled, respectively. Cooling by nanofluid at concentration (3 wt%) had the highest efficiency (19.23%). Depending on the concentrations, there is a variation in temperature between the cooling fluids' output and inlet. For the three concentrations of Titanium Oxide nanofluid (3 wt%, 2 wt%, and 1 wt%), and water, the results were (7.3, 7.8, 8.3, 8.6 °C). When the surface temperatures of the solar panels were compared to the uncooled photovoltaic panels, it was discovered that the cooling system reduced the surface temperatures by 19.0%. All of the results were obtained at 30° tilt angles with fluid rotating in two passes. The high concentration of nanofluids produced the best results, resulting in a benefit of greater heat extraction.